The study of tobacco advertisement and its contribution to the development of Malaysia football / Ahmad Amirul Firdaus Ahmad Rahiza - Ahmad Rahiza, Ahmad Amirul Firdaus (2019)
Advertising became one of the contributing factors to Malaysian football’s fame during its golden era and supporters experienced the hype during every game. During the peak of football game in Malaysia, tobacco had the biggest scale in Advertising from 1980 to 1990 before the tobacco ban in 2005. Hence, this study aims to identify the approaches applied by Tobacco Company to advertise their products during the tobacco ban era. Sports and sponsors are inseparable especially in football as it is deemed as a must: they need sponsors for the aid to support the event so the program can run smoothly and successfully. The objective of the research is to investigate the relationship between tobacco advertising and Malaysian football specifically for the Football Association of Malaysia (FAM). It was also to understand that why tobacco became main sponsors, because ironically tobacco is not a relevant product since it is unhealthy and harmful product but eventually sponsoring sports which is a healthy lifestyle game. Behind every decision and reformation, there was always somebody who took the step as a mover for an organization. Books, media and history has lifted Sultan Pahang Almarhum Sultan Haji Ahmad Shah as the only person who was the FAM President that make a good story about the Malaysia football development. However, in this research, a person who was actually the man behind the Malaysian football development will be reveal. This man is still breathing while nobody knows about his effort, stories and his contribution for his country and football. Method of data collection is through interviews involving football player, FAM representative, and the owner of advertising company who run tobacco ads during the tobacco sponsorship. This research can help us identify the impact and contribution of tobacco sponsorship in national football during its golden era. We can also find out about other brands that are involved in contributing to the improvement of football quality in Malaysia.